Therapeutic potentials of Crataegus azarolus var. eu- azarolus Maire leaves and its isolated compounds - Eman Abu-Gharbieh; Naglaa Gamil Shehab (BMC, 2017)
Abstract Background Hyperglycemia is a complicated condition accompanied with high incidence of infection and dyslipidemia. This study aimed to explore the phyto-constituents of Crataegus azarolus var. eu- azarolus Maire leaves, and to evaluate the therapeutic potentials particularly antimicrobial, antihyperglycemic and antihyperlipidemic of the extract and the isolated compound (3β-O-acetyl ursolic acid). Methods Total phenolics and flavonoidal contents were measured by RP-HPLC analysis. Free radicals scavenging activity of different extraction solvents was tested in-vitro on DPPH free radicals. The antimicrobial activity of the ethanolic extract and its fractions as well as the isolated compounds were evaluated in-vitro on variable microorganisms. Animal models were used to evaluate the antihyperglycemic and antihyperlipidemic activities of the ethanolic extract along with the isolated compound (3β-O acetyl ursolic acid). Results RP- HPLC analysis of the phenolics revealed high content of rutin, salicylic and ellagic acids. Six compounds belonging to triterpenes and phenolics were isolated from chloroform and n-butanol fractions namely: ursolic acid, 3β-O-acetyl ursolic acid, ellagic acid, quercetin 3-O-β methyl ether, rutin and apigenin7-O-rutinoside. Ethanolic extract showed the highest DPPH radical scavenger activity compared to other solvents. Ethanolic extract, hexane fraction, ursolic acid, 3β-O acetyl ursolic acid and quercetin 3-O-methyl ether showed variable antimicrobial activity against E. coli, P. aeruginosa, S. aureus, and C. albicans. Administration of the ethanolic extract or 3β-O acetyl ursolic acid orally to the mice reduced blood glucose significantly in a time- and dose-dependent manner. Ethanolic extract significantly reduced LDL-C, VLDL-C, TC and TG and increased HDL-C in rats. Ethanolic extract and 3β-O acetyl ursolic acid reduced in-vitro activity of pancreatic lipase. Conclusion This study reveals that Crataegus azarolus var. eu- azarolus Maire has the efficiency to control hyperglycemia with its associated complications. This study is the first to evaluate antihyperglycemic and antihyperlipidemic potentials of 3β-O acetyl ursolic acid.